2015
DOI: 10.3390/s150921710
|View full text |Cite
|
Sign up to set email alerts
|

Technologies for Assessment of Motor Disorders in Parkinson’s Disease: A Review

Abstract: Parkinson’s Disease (PD) is characterized as the commonest neurodegenerative illness that gradually degenerates the central nervous system. The goal of this review is to come out with a summary of the recent progress of numerous forms of sensors and systems that are related to diagnosis of PD in the past decades. The paper reviews the substantial researches on the application of technological tools (objective techniques) in the PD field applying different types of sensors proposed by previous researchers. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 113 publications
(212 reference statements)
0
36
0
Order By: Relevance
“…Nevertheless, there is a significant utility for wearable sensor technology in the movement disorders field. There has been an explosion of ongoing investigations in wearable sensors for the development of objective measures that can be used to record long-term changes [39]. Current clinical scales are assessed by scoring a video recording (examination by a specialist), who then assigns a categorical rating to each item.…”
Section: Development Of Closed-loop Dbs Systemsmentioning
confidence: 99%
“…Nevertheless, there is a significant utility for wearable sensor technology in the movement disorders field. There has been an explosion of ongoing investigations in wearable sensors for the development of objective measures that can be used to record long-term changes [39]. Current clinical scales are assessed by scoring a video recording (examination by a specialist), who then assigns a categorical rating to each item.…”
Section: Development Of Closed-loop Dbs Systemsmentioning
confidence: 99%
“…Motion tracking studies have provided guidelines to prevent sports injuries and to enhance occupational well‐being . Continuous monitoring of body movements can provide feedback on injury rehabilitation and enable early detection of disorders that affect motor control, for example, Parkinson's disease and multiple sclerosis . Furthermore, assessment of fine motor skills is one of the screening tests for conditions such as epilepsy and autism spectrum disorder (ASD) .…”
Section: Introductionmentioning
confidence: 99%
“…Using wearable devices, various studies have shown that is possible to collect objective data regarding bradykinesia, tremor, dyskinesia, walking, sleep and speech that correlate to severity of disease, response to medication and track disease progression [87][88][89][90]. A recent study also showed that an intelligent closed-loop system integrating a wide range of wearable sensors, allowed physicians to remotely monitor the condition changes of the patients, adjust medication schedules, and individualize therapy in real-life conditions [91].…”
Section: Minimising Variability / Error In Assessing Endpointsmentioning
confidence: 99%